Development of a Secure Web Application for Digital Receipt Generation with Integrated Digital Signatures - Augustine, Obayuwana; Saidu, Isah Charles; Ekwomadu, Nnaemeka Godson; Olaoluwa, Ogunleye Miracle (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
In the contemporary digital landscape, ensuring secure and efficient methods for generating and managing receipts has become increasingly critical. The rise in online transactions has amplified the need for reliable, secure, and user-friendly digital receipt systems. This project addresses this need by developing a secure web application designed for digital receipt generation, incorporating integrated digital signatures for enhanced security. The application is crafted using the Object-Oriented Analysis and Design (OOAD) methodology to ensure robustness, scalability, and maintainability. The development process involves creating an interactive front-end using HTML, CSS, and JavaScript, while the backend is built with the PHP framework. Key components of the backend include a RESTful API for receipt creation, retrieval, and digital signature operations, as well as a secure session management system. The security architecture of the system features comprehensive measures, including authentication and authorization protocols, encryption mechanisms, and the implementation of the Rivest-Shamir-Adleman (RSA) digital signature algorithm. Sensitive data, including receipt content and user information, is encrypted both at rest and in transit using SSL/TLS protocols. Additionally, RSA integration codes are utilized to protect data from third-party tampering, complemented by email authentication, hashing, and salting methods. MySQL is employed for the database management system. The results demonstrate that the developed application significantly enhances data security, with improvements in data access and retrieval processes. The integration of advanced security features ensures effective and efficient protection against data tampering, thus meeting the project's goal of providing a secure digital receipt generation system.